Analysis Noise Level in Production the Palm Oil: A Case Study - Nismah Panjaitan; Utari Noor Afifah Panggabean (Department Industrial Engineering, University of Muhammadiyah Malang, 2022)
Excessive noise exposure during the manufacturing process is a widespread issue. This research aimed to analyze noise exposure in the kernel recovery station in the manufacturing process of palm oil. We conduct some measurements and calculations for noise exposure analysis to get the Equivalent Noise Level (Leq) value during the daytime for each measurement point. The noise measurement was conducted on four machines, including a depericarper and polishing drum machine, ripple mill machine, silo dryer machine, and clay bath machine. In addition, this research showed noise contour mapping to define the noise distribution. The results of this research are that only the clay bath machine had Ls below the threshold. The clay bath machine workstation has good noise levels. The Depericarper, Polishing Drum, Ripple Mill, and Silo Dryer Machine must be quieter. Thus, this research used the Hierarchy of Control Approach to reduce and control hazardous noise exposure. The stage of HOC includes elimination, substitution, engineering, administrative control, and Personal Protective Equipment (PPE).